Assessment of Quality of Life Among Children with Inflammatory Bowel Disease - Rehman, Hooria; Cheema, Huma Arshad; Alvi, Muhammad Arshad; Anjum, Muhammad Nadeem; Fayyaz, Zafar; Batool, Syeda Sara; Saeed, Anjum (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the quality of life among children with inflammatory bowel disease (IBD) by the inflammatory bowel disease questionnaire.Study Design: Cross-sectional study.Place and Duration of the Study: Department of Pediatric Gastroenterology, Children's Hospital and Institution of Child Health, Lahore Pakistan, from Nov 2020 to Apr 2021.Methodology: A total of 60 cases (Crohn's disease or ulcerative colitis) were enrolled in the study. Quality of life was measured according to the Modified IMPACT-III questionnaire.Results: There were 38(63.3%) males and 22(36.7%) female children. The mean age was 9.57±3.40 years, while 33(55.0%) children were above ten years. The mean maternal age was found to be 37.10±4.09 years. There were 36(60.0%) children with Crohn's disease, while 24(40.0%) had ulcerative colitis. Children with Crohn's disease were found to have a significantly low quality of life compared to children in the ulcerative colitis group in the social domain (p